Strategi Pencegahan Bullying Di Lingkungan Kampus Melalui Pengggunaan Media Sosial - Maria Aufa; Fitrotus Sofiyatul Aliyah; Erina Maulidya Fachrizasalim; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Bullying in the campus environment is a problem that can disrupt the psychological and academic well-being of students. This article discusses bullying prevention strategies through the use of social media as an effective tool in creating a safe and inclusive campus environment using the library research method. Social media has an important role in students' lives, so it can be used as a medium for bullying campaigns and forming a support community for victims of bullying. In addition, clear and firm campus policies and the active role of lecturers and staff in preventing bullying are also discussed as part of a comprehensive strategy. After combining these various approaches, it is hoped that a campus environment that is free from bullying, supports positive development, and improves overall student well-being can be created.